Government agoraphobia: home bias in developing country procurement markets - Alexandros Ragoussis (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
In this paper, we present a novel set of facts on procurement openness to foreign goods and services across a large number of countries and years. In particular, we show that there is a U-shaped relationship between development levels and procurement openness, and argue that deviations in middle-income countries are associated with a distinct set of economic and institutional drivers. Besides depending on the availability of local alternatives, procurement openness in developing countries is closely associated with corruption control and decentralised governance structures. Using instrumental variables, we also demonstrate that trade agreements are not associated with convergence between private and public import intensities over time. The question of their effectiveness in middle and low-income countries thus remains open, as improvement in more fundamental institutional qualities appears to be key to minimising distortion.
Keywords: 330; Handel und Investitionen; Governance